2021
DOI: 10.1007/s10508-021-01991-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Voyeuristic and Exhibitionistic Interests: Exploring the Mediating Roles of Sociosexuality and Sexual Compulsivity from an Evolutionary Perspective

Abstract: Sociosexuality and sexual compulsivity predict sex differences in voyeuristic interest in the population. In this study, we used a sample of 1113 participants from the UK (46% men) to consider whether sociosexuality and sexual compulsivity interacted to explain these sex differences and whether this relationship extended to the related domain of exhibitionism. In doing so, we tested novel predictions derived from an evolutionary perspective which views voyeuristic and exhibitionistic interest as manifestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Increased arousal to and engagement in a wider range of sexual interests was related to increased sexual sensation seeking and compulsivity, mirroring links between hypersexuality and desires to engage in sex (Walton et al, 2016(Walton et al, , 2017. This relationship was particularly notable for fantasy arousal to and behavioral engagement in courtship paraphilias, linking to findings that these class of paraphilias are linked to compulsive sexual behaviors, hypersexuality, and behavioral disinhibition (Clark et al, 2014;Långström & Seto, 2006;Thomas et al, 2021). Similarly, increased intrusive/courtship paraphilia interests were related to more negative attitudes towards establishing consent and a perceived lack of control over establishing consent.…”
Section: Summary Of Findingsmentioning
confidence: 70%
See 1 more Smart Citation
“…Increased arousal to and engagement in a wider range of sexual interests was related to increased sexual sensation seeking and compulsivity, mirroring links between hypersexuality and desires to engage in sex (Walton et al, 2016(Walton et al, , 2017. This relationship was particularly notable for fantasy arousal to and behavioral engagement in courtship paraphilias, linking to findings that these class of paraphilias are linked to compulsive sexual behaviors, hypersexuality, and behavioral disinhibition (Clark et al, 2014;Långström & Seto, 2006;Thomas et al, 2021). Similarly, increased intrusive/courtship paraphilia interests were related to more negative attitudes towards establishing consent and a perceived lack of control over establishing consent.…”
Section: Summary Of Findingsmentioning
confidence: 70%
“…There have been some studies that demonstrated the relationship between paraphilic sexual interests and psychopathology, especially in clinical samples. Evidence suggests courtship disorders, especially exhibitionism, are related to poor socialization, compulsive sexual behavior, behavioral inhibition, and hypersexuality (Clark et al, 2014; Långström & Seto, 2006; Thomas et al, 2021). Models of sexual sadism disorder also show that psychopathic traits, behavioral disinhibition, and affective deficits are precursors to sexually sadistic behavior (Mokros et al, 2011).…”
Section: Correlates Of Paraphilic Interestsmentioning
confidence: 99%
“…To examine the interplay between positive and negative outcome expectancies on perceptions of harassment, we conducted a hierarchical regression for both sexes ( Table 3 ). We ran separate models for men and women because sex-specific analyses permit for possible sexually distinct and within-sex patterns to be observed [ 77 ]. This method of observation aligns with the goals of the current research.…”
Section: Resultsmentioning
confidence: 99%
“…A priori power analysis with G*Power (power = .90. α = .05) indicated that a sample of 99 participants was required for a multiple regression with three predictors anticipating a medium effect size. Thus, we aimed to recruit 100 participants of each sex to allow us to run sex-specific models [ 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite these gender differences, research has also shown that sociosexual orientation provides insight into various aspects of individuals' sexual behavior. For example, people with unrestricted sociosexuality tend to have lower sexual disgust, even if they have a different level of moral and pathological disgust, which can arguably help optimize their mating strategies (Al-Shawaf et al, 2015;Banai et al, 2021), and higher voyeuristic and exhibitionist behaviors (Thomas et al, 2021). These individuals are also more likely to engage in a wider array of online and offline sexual behaviors (Martins et al, 2016;Weiser et al, 2018;Zheng & Zheng, 2014) and have more risky sexual behaviors (Lopez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%